A large-scale survey on epidemiology and underreporting of needlestick and sharp injuries among healthcare workers in China - Tonghui, Wang; Ying, Liang; Xiaolu, Wu; Ming, Hao (Frontiers in Public Health, 2023)
Background Needlestick and sharp injuries (NSI) carry the risk of transmitting numerous bloodborne pathogens, leading to both health and economic burdens. The underreporting of NSIs among healthcare workers (HCWs) is a global issue of concern, as timely treatment and prevention of complications rely on proper reporting. Underreporting further impedes accurate surveillance and appropriate resource allocation, with developed and developing nations facing disparities due to differences in healthcare policy. Purpose The purpose of this research is to examine the epidemiology of NSIs and NSI underreporting, as well as to identify the determinants associated with the occurrence of NSIs and the underreporting of such injuries. Method A retrospective online survey was conducted from January 15 to January 31, 2022 among healthcare workers (HCWs) across Gansu Province, China. Results A total of 7,283 healthcare workers (HCWs) from various institutions participated in this study. After quality assurance checks, 6,464 (88.77%) responses were included in the final analysis. Results revealed a 32.86% self-reported needlestick and sharp injury (NSI) incidence among respondents, with 28.53% of NSIs going unreported. Contrary to common belief, more experienced HCWs exhibited higher rates of both NSIs and underreporting compared to their less experienced peers. The primary reasons cited for NSIs and underreporting were lapses in concentration and not perceiving patients as infectious. Multivariate regression analysis exposes the significant influence of training frequency, occupation, department and years of services on the occurrence of NSIs. Conversely, the reporting of NSIs is primarily influenced by training, reimbursement,occupation, department and hospital grade. Compared to HCWs with no training, those who received ≥3 training sessions per year showed a 12.16% lower NSI incidence (27.12% vs. 39.28%, p < 0.001) and a 55.68% lower underreporting rate (14.61% vs. 70.29%, p < 0.001). Conclusion There is a pressing need for enhanced surveillance, tailored training programs, and more efficient reporting mechanisms to combat this significant occupational health challenge.